INHIBITION OF THE GROWTH OF TOLERANT YEAST Saccharomyces cerevisiae STRAIN I136 BY A MIXTURE OF SYNTHETIC INHIBITORS - Eny Ida Riyanti; Edy Listanto (Indonesian Agency for Agricultural Research and Development, 2017)
Biomass from lignocellulosic wastes is a potential source for biobased products. However, one of the constraints in utilization of biomass hydrolysate is the presence of inhibitors. Therefore, the use of inhibitor-tolerant microorganisms in the fermentation is required. The study aimed to investigate the effect of a mixture of inhibitors on the growth of Saccharomyces cerevisiae strain I136 grown in medium containing synthetic inhibitors (acetic acid, formic acid, furfural, 5-hydroxymethyl furfural/5-HMF, and levulinic acid) in four different concentrations with a mixture of carbon sources, glucose (50 g.l-1) and xylose (50 g.l-1) at 30oC. The parameters related to growth and fermentation products were observed. Results showed that the strain was able to grow in media containing natural inhibitors (BSL medium) with µmax of 0.020/h. Higher level of synthetic inhibitors prolonged the lag phase, decreased the cell biomass and ethanol production, and specific growth rate. The strain could detoxify furfural and 5-HMF and produced the highest ethanol (Y(p/s) of 0.32 g.g-1) when grown in BSL. Glucose was utilized as its level decreased in a result of increase in cell biomass, in contrast to xylose which was not consumed. The highest cell biomass was produced in YNB with Y (x/s) value of 0.25 g.g-1. The strain produced acetic acid as a dominant side product and could convert furfural into a less toxic compound, hydroxyl furfural. This robust tolerant strain provides basic information on resistance mechanism and would be useful for bio-based cell factory using lignocellulosic materials.